Nontraumatic dental condition-related visits to emergency departments on weekdays, weekends and night hours: findings from the National Hospital Ambulatory Medical Care survey - Okunseri, Christopher (Dove Medical Press, 2013)
OBJECTIVE: To determine whether the rates of nontraumatic dental condition (NTDC)-related emergency department (ED) visits are higher during the typical working hours of dental offices and lower during night hours, as well as the associated factors. METHODS: We analyzed data from the National Hospital Ambulatory Medical Care Survey for 1997 through 2007 using multivariate binary and polytomous logistic regression adjusted for survey design to determine the effect of predictors on specified outcome variables. RESULTS: Overall, 4,726 observations representing 16.4 million NTDC-related ED visits were identified. Significant differences in rates of NTDC-related ED visits were observed with 40%–50% higher rates during nonworking hours and 20% higher rates on weekends than the overall average rate of 170 visits per hour. Compared with 19–33 year olds, subjects < 18 years old had significantly higher relative rates of NTDC-related ED visits during nonworking hours [relative rate ratio (RRR) = 1.6 to 1.8], whereas those aged 73 and older had lower relative rates during nonworking hours (RRR = 0.4; overall P = 0.0005). Compared with those having private insurance, Medicaid and self-pay patients had significantly lower relative rates of NTDC visits during nonworking and night hours (RRR = 0.6 to 0.7, overall P < 0.0003). Patients with a dental reason for visit were overrepresented during the night hours (RRR = 1.3; overall P = 0.04). CONCLUSION: NTDC-related visits to ED occurred at a higher rate during nonworking hours and on weekends and were significantly associated with age, patient-stated reason for visit and payer type.